Evaluating Hypertension Management at a Student Run Free Clinic in Alabama - Sowell, Josiah; Wagner, Grant; Chambers, Emmie; Van Wagoner, Nicholas (Journal of Student-Run Clinics, 2024)
Background: Healthcare remains unavailable for many persons who are un- or under-insured. Equal Access Birmingham (EAB) is a student run free clinic that provides urgent, primary, and specialty care to the Birmingham area. The purpose of this study was to evaluate EAB’s effectiveness in hypertension management. Methods: A total of 137 patient records were identified with hypertension. After exclusion criteria were applied, the cohort consisted of 66 patients. The average number of clinic visits per patient was 6.4 (standard deviation [SD] ± 4.1). Results: Systolic blood pressure decreased from 151.3mmHg to 140.6mmHg (p=0.0028, t(64)=2.95, 95% confidence interval [CI] 3.82, 17.57). Diastolic blood pressure decreased from 90.7mmHg to 85.5mmHg (p=0.0120, t(64)=2.37, 95% CI 1.18, 9.27). Conclusions: In patients with consistently recorded vital signs that followed up with regular clinic visits, blood pressure over time was significantly reduced. However, many patients were lost to follow up.